Experience and teleology in ancient historiography 'futures past' from Herodotus to Augustine - Grethlein, Jonas 1978- (Cambridge University Press, 2013)
The past is narrated in retrospect. Historians can either capitalize on the benefit of hindsight and give their narratives a strongly teleological design or they may try to render the past as it was experienced by historical agents and contemporaries. This book explores the fundamental tension between experience and teleology in major works of Greek and Roman historiography, biography and autobiography. The combination of theoretical reflections with close readings yields a new, often surprising assessment of the history of ancient historiography as well as a deeper understanding of such authors as Thucydides, Tacitus and Augustine. While much recent work has focused on how ancient historians use emplotment to generate historical meaning, Experience and Teleology in Ancient Historiography offers a new approach to narrative form as a mode of coming to grips with time
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; History, Ancient / Historiography; Rhetoric, Ancient / Historiography; History / Methodology; Erfahrung; Antike; Teleologie; Geschichtsschreibung